Netralitas Aparatur Sipil Negara Dalam Pemilihan Umum Kepala Daerah Kabupaten Asahan Tahun 2020 - Hanifah Sadikin; Subhilhar Subhilhar; Heri Kusmanto (Universitas Medan Area, 2022)
This study aims to find out and analyze the neutrality of the State Civil Apparatus in the 2020 Asahan district head election as well as to describe and analyze what factors and obstacles to the non-neutrality of the state civil apparatus in the 2020 Asahan District Head General Election. The type of research used is descriptive qualitative with descriptive analytical method. This study uses a qualitative approach that produces descriptive data in the form of recording researchers and facts that will be found in the field. This study uses the theory of bureaucracy according to Weber (1974) and the theory of neutrality according to Amin which states that neutral means not taking sides and not being involved. The results of this study revealed a lack of neutrality for ASN in Asahan Regency as evidenced by violations involving 8 ASN and field facts based on observations and interviews. Meanwhile, the factors that lead to the occurrence of violations are the position factor and the group similarity factor. From the research that has been carried out, it was found that the application of this neutrality rule has obstacles in the form of obstacles from the ASN body itself, the suboptimal monitoring system carried out by Bawaslu and KASN, public understanding of ASN neutrality, and the absence of a budget for monitoring ASN neutrality in the PILKADA of the Asahan Regency Government.